2008
DOI: 10.1016/j.bbamem.2008.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Alzheimer's Aβ(25–35) peptide and phospholipid bilayers: The role of cholesterol

Abstract: There is mounting evidence that the lipid matrix of neuronal cell membranes plays an important role in the accumulation of beta-amyloid peptides into senile plaques, one of the hallmarks of Alzheimer's disease (AD). With the aim to clarify the molecular basis of the interaction between amyloid peptides and cellular membranes, we investigated the interaction between a cytotoxic fragment of Abeta(1-42), i.e., Abeta(25-35), and phospholipid bilayer membranes. These systems were studied by Electron Paramagnetic Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
89
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(108 citation statements)
references
References 45 publications
19
89
0
Order By: Relevance
“…These findings where confirmed for the same peptide fragment, via electron paramagnetic resonance spectroscopy on spin-labeled phospholipid acyl tails, which showed that cholesterol, and not leaflet charge, affects the ability of Ab fragments to insert (50). Our results are fully consistent with these experimental studies in that the C-terminus of Ab does embed into the membrane, but the N-terminus is exposed to the extracellular space.…”
Section: Discussionsupporting
confidence: 92%
“…These findings where confirmed for the same peptide fragment, via electron paramagnetic resonance spectroscopy on spin-labeled phospholipid acyl tails, which showed that cholesterol, and not leaflet charge, affects the ability of Ab fragments to insert (50). Our results are fully consistent with these experimental studies in that the C-terminus of Ab does embed into the membrane, but the N-terminus is exposed to the extracellular space.…”
Section: Discussionsupporting
confidence: 92%
“…This evidence indicates that A β (25–35) is inserted in the bilayer positioning between the outer part of the hydrophobic core and the external hydrophilic layer. A similar solubilization site was already observed in other lipid systems5863. When A β (25–35) is added to the lipid bilayers in the presence of curcumin or its analogues, the 5-PCSL spectrum is much less affected, and in some cases, no variation is observed (see Table 2SI).…”
Section: Resultssupporting
confidence: 77%
“…Aβ 1-40 is a more abundant species, whereas Aβ 1-42 is a more neurontoxic species. Recent studies [2][3][4][5] have proposed that the mechanism of Aβ-mediated toxicity is correlated with its ability to disrupt the integrity and permeability of cell membrane. Under different experimental conditions, Aβ peptides can either penetrate into membrane to form ion channels/pores 6,7 or associate with the membrane surface to induce membrane thinning.…”
Section: Introductionmentioning
confidence: 99%